Underwater dispersion-resistant high-strength grouting material and preparation method thereof
Through nanomaterial predispersion and lignocellulose modification technology, combined with corrosion inhibitor design, the problems of dispersion resistance, early strength and durability of underwater grouting materials are solved, efficient underwater repair and long-term stability are achieved, and the shortcomings of traditional processes are overcome.
Patent Information
- Application Number
- CN202510841981.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-23
- Publication Date
- 2025-09-02
- Estimated Expiration
- 2045-06-23
AI Technical Summary
Existing underwater grouting materials have shortcomings in dispersion resistance, early strength, durability and construction efficiency, which are difficult to meet the needs of rapid repair and long-term service. In addition, traditional processes have risks of nanomaterial agglomeration, component segregation and environmental protection.
Using nanomaterial predispersion technology, lignocellulose modification and corrosion inhibitor molecular design, a multi-stage protection system is built through ultrasonic treatment, vacuum impregnation and microwave curing processes to improve the material's dispersion resistance, early strength and durability, and optimize construction performance.
It significantly improves the dispersion resistance and early strength of underwater grouting materials, meets the needs of rapid repair, ensures long-term durability, reduces environmental protection risks, and improves construction efficiency.
Smart Images

Figure CN120574008A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to an underwater anti-dispersion high-strength grouting material and a preparation method thereof. Background Art
[0002] The development of underwater engineering repair materials has evolved from traditional concrete to specialized grouting materials. Early underwater repairs primarily utilized ordinary Portland cement-based materials, but these faced core challenges such as slow strength development, poor dispersion resistance, and insufficient durability. With the growing demand for large-scale infrastructure construction, such as marine engineering and water conservancy hubs, underwater grouting materials face even more stringent technical challenges in terms of scour resistance, early strength development mechanisms, and long-term stability.
[0003] Traditional formulations often combine a single natural mineral admixture (such as fly ash or mineral powder) with a conventional water reducer. As described in patent CN105622006B, their 1-day compressive strength at 5°C is only 15 MPa, and their 28-day strength is 35 MPa, making them inadequate for rapid repairs. Furthermore, the underwater anti-dispersion loss rate of these materials generally exceeds 25%, resulting in significant loss of active ingredients. Although CN106747146A explored combining sulfoaluminate cement with an anti-dispersion agent, its 28-day compressive strength remains limited to below 60 MPa, and the performance unevenness caused by nanomaterial agglomeration remains unresolved. Existing technologies often rely on polymers (such as UWB-II and cellulose ethers) to form a physical shielding layer, a single mechanism that easily fails under dynamic water flow conditions. Experimental data shows that the anti-dispersion efficiency of traditional materials decreases by over 40% when flow rates exceed 1.5 m / s. In addition, excessive polymer incorporation (>3wt%) will significantly delay the setting time. For example, a literature report that adding 4% polyacrylamide will extend the initial setting time to 12 hours, seriously affecting construction efficiency. The chloride ion permeability coefficient in the marine environment is a key indicator for evaluating the durability of materials. Existing grouting materials generally contain Cl - Diffusion coefficient>5×10 -12 m 2 / s, making it difficult to meet the 50-year service life requirement. Although CN105622006B attempted to introduce nano-calcium silicate hydrate, its preparation process failed to address the stability of the nanoparticles in alkaline environments, resulting in a late-stage strength reduction of 15%. Traditional dry mixing processes suffer from component segregation, resulting in poor mixing uniformity of materials with large particle size differences (such as cement and expansive agents), with a coefficient of variation as high as 8.3%. Wet processes face challenges dispersing nanomaterials. Conventional stirring (<500 rpm) is unable to break up nano-silica agglomerates, resulting in actual material performance reaching only 60-70% of the theoretical value. Some patents utilize ultrasonic dispersion, but fail to establish a quantitative relationship between power, frequency, and time, resulting in low energy efficiency. Existing technologies often employ a "superposition process," such as simply combining an accelerator with an anti-dispersion agent, lacking molecular-level coordinated design. A typical example is the composite accelerator of calcium nitrate and calcium formate, which, while improving early strength, can exacerbate slurry settling and segregation (bleeding rate >2.5%). In addition, corrosion inhibitors mostly use nitrite compounds, which pose environmental risks and have poor compatibility with cellulose anti-dispersants.
[0004] The proposal of this invention is based on a systematic study of the above-mentioned materials mechanism, process engineering and actual application scenarios. Through innovative nano-composite technology, biomass fiber modification and corrosion inhibitor molecular design, a multi-level protection system is constructed to break through the performance defects of existing technologies. Summary of the Invention
[0005] Traditional underwater grouting materials have poor anti-dispersion properties, with anti-dispersion loss rates generally exceeding 25%. Under dynamic water flow conditions (flow rate >1.5m / s), performance drops by more than 40%. Early strength development is slow. For example, the 1-day compressive strength at 5°C is only about 15MPa, and the 28-day strength is limited to 35-60MPa, making it difficult to meet rapid repair needs. Durability is insufficient, and the chloride ion diffusion coefficient is high, making it difficult to guarantee a 50-year service life. Nanomaterial agglomeration leads to uneven performance, and conventional mixing makes it difficult to break up the agglomerates, with actual performance reaching only 60-70% of the theoretical value. Excessive use of high-molecular polymer anti-dispersants (>3wt%) prolongs the initial setting time (e.g., to 12h), affecting construction efficiency. Traditional corrosion inhibitors (such as nitrites) pose environmental risks and have poor compatibility with cellulose anti-dispersants. The dry mixing process suffers from severe component segregation, the wet mixing process has low nano-dispersion efficiency, and lacks molecular-level collaborative design.
[0006] To solve the above problems, the present invention adopts the following technical solutions.
[0007] A method for preparing an underwater anti-dispersion high-strength grouting material comprises the following steps: (1) pre-dispersion treatment of nanomaterials: selecting nanomaterials, wherein the nanomaterials are nano-silicon dioxide, nano-iron oxide or nano-aluminum oxide, adding a dispersant and water and dispersing by ultrasonication to obtain a nano-dispersion liquid; (2) dry mixing of matrix materials: weighing 20-40 parts by weight of sulphoaluminate cement clinker or silicate cement, 6-12 parts by weight of ultrafine mineral powder, 4-10 parts by weight of active steel slag or silica fume, 10-25 parts by weight of fly ash or ultrafine fly ash, and 1-3 parts by weight of bentonite in proportion, and mixing them in a spiral mixer. Form a uniform dry mixed base; (3) wet mixing of the mixture: add the nano-dispersion prepared in step (1) to the dry mixed base formed in step (2), and at the same time introduce an early strength agent, an expander, lignocellulose, and a retarder, and then stir to obtain a mixture; wherein the preparation method of lignocellulose is as follows: select agricultural waste rice husks or wheat straws, add water to obtain a slurry with a solid content of 3-5wt%, add 2% of cellulase (endoglucanase, number: EC3.2.1.4) at a final mass percentage, and react for 2-3h at 45-50℃ and pH4.5-5.0, using a power Ultrasonic treatment at 600-800W and frequency of 20kHz for 10-15min was performed to obtain nanocellulose with a diameter of 10-50nm and an aspect ratio greater than 30. A 10mM nano-aluminum hydroxide solution (particle size 10-50nm) was prepared and embedded into the microporous structure of the nanocellulose by vacuum impregnation. The amount of nano-aluminum hydroxide solution was 10 times that of the nanocellulose. The vacuum impregnation pressure was 0.1-0.3MPa and the time was 30-60min. Microwave-assisted curing was then performed at a curing power of 800W for 3-5min. Then, nano-aluminum hydroxide was added. 4-cyano-1H-1,2,3-triazole (CAS No. 32979-77-4) with a mass of 3-6 times that of rice cellulose and water with a mass of 30-40 times that of nanocellulose are controlled at a reaction condition of 60-80°C for a time of 1-2h, and then dried under vacuum (not exceeding 80°C) to obtain a slurry; (4) Optimized preparation of wet mixed slurry: water, the mixture obtained in step (3) and a corrosion inhibitor are added to a pulping device, and the mass ratio of water, the mixture and the corrosion inhibitor is controlled to be 1: (0.25-0.35): (0.05-0.1), and then stirred and temperature controlled simultaneously to obtain a slurry.
[0008] Ultrasonic cavitation effect: Ultrasonic treatment at 500-800W and 40-60kHz for 10-30 minutes breaks down the van der Waals aggregation of the nanoparticles through the localized high temperature and high pressure generated by the collapse of cavitation bubbles. The hydrophobic chains (C12-C18) of the polyether water-reducing agent adsorb the nanoparticles, while the hydrophilic groups form an electrical double layer with a zeta potential exceeding -35mV, ensuring dispersion stability. Size matching effect: Nanomaterials with a particle size of 10-50nm form a graded filling with the cement hydration product CSH gel (average pore size of 5nm), reducing the porosity of traditional materials from 18% to 9.5% and increasing compressive strength by 40%. Enzymatic hydrolysis-ultrasound coupling: Cellulase (EC3.2.1.4) selectively cleaves β-1,4-glycosidic bonds at 45-50°C and pH 4.5-5.0, combined with shear forces generated by 600-800W ultrasound, dissociating rice husk fibers into nanofibers with a diameter of 10-50nm and an aspect ratio greater than 30. Vacuum impregnation strengthening: 0.1-0.3MPa negative pressure makes the dispersion (15-40nm) penetrate into the cellulose micropores (2-5nm), 800W microwave induces Al-OC covalent bond, and the interface bonding energy is increased from 50J / m 2 Increased to 210J / m 2 . 4-Cyano-1H-1,2,3-triazole is grafted with cyanide groups on the fiber surface through a click chemistry reaction, and the contact angle is reduced from 75° to 28°, thereby improving the compatibility with the cement matrix. Synergistic effect of early strength agent: Sodium sulfate, sodium formate, and sodium nitrate are compounded in proportion, and the hydration degree of sulfoaluminate cement is increased from 35% to 62% in 1 hour at 5°C. XRD shows that the early strength agent promotes the formation of calcium aluminoferrite crystal nuclei, and DSC detects that the hydration exothermic peak is advanced by 2.8 hours. Expansion compensation mechanism: Quicklime reacts with water, and the volume expansion rate reaches 120%, compensating for shrinkage strain. Synchrotron radiation micro-CT shows that the addition of 3-7% quicklime reduces the 28d shrinkage rate from 0.25% to 0.08%, and the pore tortuosity increases by 3.2 times. Iron-based precursor transformation: The iron-based material forms a colloid in ammonia water, diethyl carbonate is hydrolyzed to form carbonate ions, and a core-shell structure is generated by hydrothermal reaction at 140-180°C. Ethyl orthosilicate is polycondensed to form a 2-3nm mesoporous silica layer, which greatly increases its specific surface area. Dopamine polymerization: Under pH 5, dopamine is oxidized to form polydopamine (PDA). - The accumulation and hydrogen bonding form a 5-8nm coating on the Fe3O4 surface. XPS analysis shows that the C=N content of PDA is 28.6%, forming a conjugated system with the o-quinone structure generated by sodium iodate oxidation, making Cl - The diffusion coefficient is from 5.2×10 - 12 m 2 / s dropped to 1.8×10 -12 m 2 / s. The slurry yield stress during the wet mixing stage was reduced from 85Pa in the traditional formulation to 32Pa, and the thixotropic index was increased from 2.1 to 4.7. Laser particle size analysis showed that this process reduced the particle size (D50) from 45μm to 18μm, maintaining the zeta potential above -25mV, ensuring a dispersion resistance loss rate of less than 5% during underwater injection.
[0009] The parameters and properties of sulphoaluminate cement clinker are as follows: Sulphoaluminate cement clinker, primarily composed of calcium sulphoaluminate, is typically used for rapid hardening, high strength, and corrosion resistance, such as in underwater applications. Main minerals (by weight): Calcium sulphoaluminate: 50-70%, providing rapid hydration. Anhydrous calcium sulphoaluminate: 20-30%, enhancing early strength.
[0010] The properties of Portland cement are as follows: Portland cement, composed primarily of tricalcium silicate and dicalcium silicate, is the most commonly used type of cement, widely used in general-purpose concrete and grouting materials. Main minerals (by weight): Tricalcium silicate: 50-70%, provides early strength; Dicalcium silicate: 15-30%, provides long-term strength; Tricalcium aluminate: 5-12%, affects setting speed; Tetracalcium aluminoferrite: 5-15%, improves durability.
[0011] The parameters of the ultrafine mineral powder are as follows: Chemical composition (mass percentage): silicon dioxide: 30-40%, aluminum oxide: 10-20%, calcium oxide: 30-45%, magnesium oxide: 5-10%.
[0012] The parameters and properties of active steel slag are as follows: Active steel slag is a by-product of the steelmaking process. Its chemical composition (mass percentage) is: calcium oxide: 40-50%, silicon dioxide: 15-25%, iron oxide: 10-20%, aluminum oxide: 5-10%, and magnesium oxide: 5-10%.
[0013] Silica fume (also known as microsilica powder) is a highly reactive silica fume produced during the smelting of ferrosilicon or silicon metal. Its chemical composition (by mass) is: 85-95% silicon dioxide, ≤1% aluminum oxide, ≤1% calcium oxide, and ≤2% potassium oxide.
[0014] The parameters and properties of fly ash are as follows: Fly ash is the fine ash collected from the flue gas of coal-fired power plants. Its chemical composition (mass percentage) is: silicon dioxide: 40-60%, aluminum oxide: 20-35%, iron oxide: 5-15%, and calcium oxide: 2-10%.
[0015] The parameters and properties of ultrafine fly ash are as follows: Chemical composition (mass percentage): silicon dioxide: 50-70%, aluminum oxide: 25-35%, iron oxide: 5-15%, calcium oxide: 2-10%.
[0016] Bentonite's properties are as follows: Bentonite is a clay mineral primarily composed of montmorillonite, which has high water absorption and swelling properties. Its chemical composition (by mass) is as follows: 55-65% silicon dioxide, 15-20% aluminum oxide, 1-5% calcium oxide, and 2-4% sodium oxide.
[0017] The mechanism of wood cellulose is as follows: enzymatic hydrolysis-ultrasonic coupled dissociation: Action: Cellulase (endoglucanase, EC3.2.1.4) selectively cuts the β-1,4 glycosidic bonds in cellulose molecules at 45-50°C and pH 4.5-5.0, reducing crystallinity (CO-C bond strength decreases by 62%). Ultrasonic waves (600-800W, 20kHz) generate high shear forces through cavitation effect, dissociating fiber bundles into nanofibers with a diameter of 10-50nm, increasing the specific surface area to 380m 2 / g (surface roughness reduced to 3nm). Significance in grouting materials: The high specific surface area and three-dimensional network structure of the nanofibers enhance the cohesion of the grout, significantly reducing the dispersion loss of the material in underwater environments (anti-dispersion loss rate <5%). Significance in grouting materials: Strengthens the interfacial bonding between the fibers and the cement matrix, achieving a shear strength of 35MPa (a 337% increase compared to untreated fibers), improving the crack resistance and mechanical properties of the grout. Triazole grafting surface modification: Effect: 4-Cyano-1H-1,2,3-triazole is grafted with cyano groups via a click chemistry reaction (N1s peak intensity increases by 28.6%), reducing the contact angle to 28° and improving hydrophilicity. The molecular brush structure increases the zeta potential to -32mV and prolongs the suspension stability time to 72h. Significance in grouting materials: Improves the compatibility of nanocellulose with the cement matrix, enhances the uniformity and stability of the grout, and reduces segregation during underwater construction. Multi-scale structural synergistic effect: Effect: The graded filling of alumina particles and cellulose micropores reduces porosity to 9.5% and increases compressive strength by 40%. The interfacial stress transfer efficiency between the modified fibers and the matrix is high, increasing fracture energy absorption by sixfold. Significance in grouting materials: Multi-scale optimization enables the grout to combine high strength (28-day compressive strength >60 MPa) with low porosity, meeting the requirements for rapid repair and long-term durability in underwater projects. As a key component in grouting materials, lignocellulose significantly enhances material properties through the following mechanisms: Anti-dispersion: The three-dimensional network and modified hydrophilicity of nanocellulose effectively prevent grout loss in dynamic water flow, resulting in an anti-dispersion loss rate far lower than the 25% of traditional materials. Enhanced strength: The interfacially reinforced fibers enhance the matrix's crack resistance and toughness. In synergy with the accelerator and expansion agent, the 1-day compressive strength exceeds 15 MPa at 5°C, and the 28-day strength exceeds 60 MPa. Durability: The low porosity of the fiber and the synergistic effect with the corrosion inhibitor reduce the chloride ion diffusion coefficient to 1.8×10 -12 m 2 / s, ensuring a 50-year service life. Construction performance: The dispersion stability of the modified fiber optimizes the fluidity of the slurry (yield stress reduced to 32Pa, thixotropic index increased to 4.7), facilitating underwater pouring.
[0018] Preferably, the particle size of the nano-silicon dioxide in step (1) is 10-30 nm; the particle size of the nano-iron oxide in step (1) is 20-50 nm; the particle size of the nano-aluminum oxide in step (1) is 15-40 nm; and the dispersant in step (1) is a polyether water reducer (allyl polyethylene glycol ether, CAS No.: 27274-31-3) or a zwitterionic water reducer (lauryl hydroxysulfobetaine, CAS No.: 13197-76-7).
[0019] Preferably, the parameters of ultrasonic dispersion in step (1) are as follows: power 500-800 W, frequency 40-60 kHz, time 10-30 min; the mass ratio of the nanomaterial, dispersant and water in step (1) is (3-6): (10-20): (60-100).
[0020] Preferably, the rotation speed of the spiral stirrer in step (2) is 50-100 rpm, and the mixing time is 5-10 min.
[0021] Preferably, in step (3), the mass ratio of the dry-mix base material, the nano-dispersion, the early strength agent, the expansion agent, the lignocellulose, and the retarder is 100: (1.5-4): (5-10): (3-7): (1.5-3): (0.05-0.2); wherein the expansion agent is quicklime, wherein the aspect ratio of the lignocellulose is greater than 30, and wherein the retarder is sodium citrate.
[0022] Preferably, the early strength agent in step (3) is a mixture of sulfate, formate, and nitrate in a mass ratio of (0.4-1): (0.5-1.5): (0.5-1); the stirring speed in step (3) is 100-200 rpm, and the stirring time is 5-8 minutes. The sulfate, formate, and nitrate are all in the form of sodium salts.
[0023] Preferably, the stirring speed in step (4) is 200-400 rpm, and the stirring time is 3-5 min; the temperature controlled in step (4) is 30-40°C.
[0024] Preferably, the preparation method of the corrosion inhibitor in step (4) is as follows: ferrous sulfate, ferrous chloride and water are mixed in a mass ratio of 1: (1-1.5): (80-100), heated in a water bath to 60-80°C, then 20% ammonia solution with a mass percentage of 3-7 times the mass of ferrous sulfate and diethyl carbonate (CAS No.: 105-58-8) with a mass percentage of 2-4 times the mass of ferrous sulfate are added, stirred at 200-300rpm for 10-20min, then transferred to a high temperature and high pressure reactor, reacted at 140-180°C for 6-12h, cooled and recovered the supernatant, and added to the above Ethyl orthosilicate (CAS No. 78-10-4) in an amount 0.1-0.2 times the mass of the supernatant is shaken at 60 rpm overnight and dried to obtain a primary product. Then, water in an amount 80-150 times the mass of the primary product is added and the pH is adjusted to 5. Dopamine (CAS No. 51-61-6) in an amount 0.2-0.6 times the mass of the primary product and sodium iodate (CAS No. 7681-55-2) in an amount 0.1-0.2 times the mass of the primary product are added. After stirring and mixing, the mixture is reacted in a microwave oven at 200-300 W for 5-15 minutes, naturally cooled, and dried to obtain the final product.
[0025] The preparation mechanism of this corrosion inhibitor achieves multi-level protection of metal surfaces through multi-step synergistic action. Its core mechanism can be divided into the following four levels: Iron-based precursor conversion mechanism: Colloid formation: Ferrous sulfate and ferrous chloride generate [Fe(OH)2] in ammonia solution + Colloid, carbonate ions generated by the hydrolysis of diethyl carbonate, form a core-shell structure under hydrothermal conditions at 140-180°C. Synchrotron radiation shows that it corresponds to a spinel structure. Mesoporous coating: Ethyl orthosilicate is condensed under acidic conditions to form a 2-3nm mesoporous silica layer with a specific surface area of 650m 2 / g, the pore size distribution is concentrated at 3.8nm, providing Cl - Adsorption sites. Polydopamine interface engineering: Oxidative polymerization: Under pH 5 conditions, dopamine is oxidized by sodium iodate to form polydopamine (PDA), in which the C=N bond content reaches 28.6%, and the quinone structure accounts for 42%, forming a conjugated electron system. Interface binding: PDA forms Fe-O bonds with the Fe3O4 surface through the catechol group (binding energy 532.1eV), and at the same time produces hydrogen bonds with SiO2, and the contact angle increases from 75° to 112°, significantly enhancing the hydrophobicity. Corrosion inhibition synergistic effect: Physical barrier: The core-shell structure (particle size 50-80nm) fills the pores of the cement matrix. The total porosity measured by mercury intrusion method is reduced from 18% to 9.5%, and the tortuosity is increased by 3.2 times. Electrochemical inhibition: The quinone / hydroquinone redox pair of PDA provides an electron transfer channel, which shifts the corrosion potential of carbon steel positively by 120mV and the corrosion current density from 5.6μA / cm 2 Down to 0.8μA / cm 2Ion chelation: Silane groups on the surface of silica and Cl - Hydrogen bonds are formed, and the Zeta potential increases from -25mV to -8mV. - The diffusion coefficient is from 5.2×10 -12 m 2 / s dropped to 1.8×10 -12 m 2 / s. Process enhancement mechanism: Microwave-induced cross-linking: 200-300W microwaves induce high-frequency oscillation (2.45GHz) of polar molecules, which increases the cross-linking degree of PDA by 38%. The CNC stretching vibration peak (1250cm -1 ) strength increased by 2.3 times. Hierarchical structure construction: Vacuum impregnation (0.1-0.3MPa) ensures >92% penetration into cellulose micropores (2-5nm), and interfacial shear strength reaches 35MPa, a 337% increase compared to untreated samples. This corrosion inhibitor utilizes multiple mechanisms of chemical bonding, physical filling, and electrochemical protection to construct a three-level protection system from nanoscale to mesoscale to macroscale on the metal surface, breaking through the limitations of traditional single-action corrosion inhibitors.
[0026] An underwater anti-dispersion high-strength grouting material is obtained by the above-mentioned preparation method.
[0027] Compared to existing technologies, this invention offers significant benefits: Dispersion resistance is significantly improved: Through pre-dispersion treatment with nanomaterials (silicon dioxide, iron oxide, or aluminum oxide) and the introduction of lignocellulose, the grout's dispersion resistance in underwater environments is significantly enhanced. The uniform dispersion of the nanomaterials enhances the matrix's density, while the three-dimensional network structure of the lignocellulose improves cohesion, effectively preventing material loss in water. Compared to the >25% loss of dispersion resistance experienced by conventional materials under dynamic water flow conditions, this invention reduces this loss to <5%, significantly improving the reliability of underwater construction.
[0028] Both early and late strength are significantly improved: The synergistic effect of an early-strength agent (a mixture of sodium sulfate, sodium formate, and sodium nitrate) and an expansive agent (quicklime) accelerates the cement hydration reaction, increasing early strength. The expansive agent also compensates for shrinkage, ensuring a steady increase in late-stage strength. Compared to existing technologies with a 1-day compressive strength of only 15 MPa and a 28-day strength of 35-60 MPa at 5°C, this invention significantly improves strength, meeting the needs of rapid repair and long-term service in underwater projects.
[0029] Durability is greatly improved: Through the molecular design of the corrosion inhibitor, dopamine and sodium iodate are used for modification to form a dense protective layer, which effectively inhibits the penetration of chloride ions, ensures the long-term stability of the material in the marine environment, and meets the 50-year service cycle requirement.
[0030] Optimized construction performance: Through optimized preparation of wet-mix slurry, the mass ratio of water, mixture and corrosion inhibitor is controlled to 1: (0.25-0.35): (0.05-0.1), and stirring is carried out at 200-400rpm and 30-40℃. This ensures good fluidity of the slurry, avoids the problem of excessive use of traditional polymer anti-dispersants (>3wt%) causing the initial setting time to be extended to 12 hours, and maintains a suitable construction window.
[0031] Improved environmental protection: The corrosion inhibitor is modified with dopamine and sodium iodate, replacing the traditional nitrite corrosion inhibitor, reducing environmental risks and complying with the development trend of green building materials.
[0032] Process innovation: Nanomaterial pre-dispersion technology and cellulose modification processes (including enzymatic hydrolysis, ultrasonic treatment, vacuum impregnation, microwave curing and triazole modification) solve the problems of nanomaterial agglomeration and insufficient interfacial bonding between fibers and the matrix, ensuring the uniformity and stability of material properties and overcoming the defects of component segregation in traditional dry mixing processes and low dispersion efficiency in wet mixing processes.
[0033] In summary, the present invention comprehensively improves the anti-dispersion, strength, durability, construction performance and environmental protection of underwater grouting materials through various technical innovations, overcomes the defects of the existing technology, and has significant practical value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a scanning electron microscope image of the lignocellulose prepared in Example 1.
[0035] Figure 2 This is a scanning electron microscope image of the corrosion inhibitor prepared in Example 1.
[0036] Figure 3 This is a scanning electron microscope image of the slurry prepared in Example 1. DETAILED DESCRIPTION
[0037] The present invention is described in detail below through specific examples. However, the purpose and application of these exemplary embodiments are intended solely to illustrate the present invention and are not intended to limit the actual scope of protection of the present invention in any manner, nor to restrict the scope of protection of the present invention to these examples. For parameter ranges not specified, intermediate values are used. Furthermore, for mass percentages or weight percentages not explicitly stated or mentioned, they generally refer to the final concentration after addition. The dispersant is a polyether water reducer (allyl polyglycol ether, CAS No.: 27274-31-3) or a zwitterionic water reducer (lauryl hydroxysulfobetaine, CAS No.: 13197-76-7).
[0038] Example 1
[0039] Pre-dispersion treatment of nanomaterials: Take 3 g of nano-silicon dioxide (particle size 10 nm), add 10 g of polyether water reducer and 60 g of water, and disperse under 500 W, 40 kHz ultrasonic conditions for 10 min to prepare a nano-dispersion liquid.
[0040] Dry mix preparation of base materials: 20 g of sulphoaluminate cement clinker, 6 g of ultrafine mineral powder, 4 g of activated steel slag, 10 g of fly ash and 1 g of bentonite were mixed in a spiral mixer at 50 rpm for 5 min to form a dry mix base material.
[0041] Wet preparation of the mixture: Preparation of cellulose: Pulp rice husk (solid content 3wt%), add 2% of cellulase (EC3.2.1.4) to the mixture, react at 45℃, pH4.5 for 2h, ultrasonically treat at 600W, 20kHz for 10min to obtain nanocellulose (diameter 10nm, aspect ratio 35). Prepare nano-aluminum hydroxide solution (particle size 15nm), vacuum impregnate at 0.1MPa for 30min, microwave cure at 800W for 3min, add 4-cyano-1H-1,2,3-triazole (3 times the mass of nanocellulose) and water (30 times the mass of nanocellulose), react at 60℃ for 1h, and vacuum dry to obtain 1.5g of cellulose, the scanning electron microscope image of which is shown as follows. Figure 1 shown.
[0042] Take 100 g of dry mixed base, add 1.5 g of nano-dispersion, 5 g of early strength agent (the mass ratio of sodium sulfate, sodium formate, and sodium nitrate is 0.4:0.5:0.5), 3 g of expansion agent (quicklime), 1.5 g of wood cellulose, and 0.05 g of retarder (sodium citrate), and stir at 100 rpm for 5 minutes to obtain a mixture.
[0043] Optimized preparation of wet mixed slurry: Preparation of corrosion inhibitor: Take 1g of ferrous sulfate, 1g of ferrous chloride, and 80g of water, heat in a water bath at 60℃, add 3g of 20% by mass ammonia solution and 2g of diethyl carbonate, stir at 200rpm for 10min, react at 140℃ under high pressure for 6h, recover the supernatant, add ethyl orthosilicate (0.1 times the mass of the supernatant), shake at 60rpm overnight, and dry to obtain the primary product. Add water (80 times the mass of the primary product), adjust the pH to 5, add dopamine (0.2 times the mass of the primary product) and sodium iodate (0.1 times the mass of the primary product), react at 200W microwave for 5min, and dry to obtain the corrosion inhibitor, such as Figure 2 shown.
[0044] Take 100g of water, 25g of mixed material, 5g of corrosion inhibitor, stir at 200rpm for 3min, control the temperature at 30℃, and obtain the final slurry. Figure 3 As shown, it can be seen that there are fewer voids on the surface and the overall structure is relatively compact.
[0045] Example 2-15
[0046] Examples 2-15 refer to the process flow of Example 1, with some parameters adjusted. The specific formulas and process parameters are shown in Tables 1 and 2. The parameters cover the endpoint values and intermediate values in the claims to ensure the correct mass ratio.
[0047] Comparative Examples 1-18
[0048] In order to verify the necessity of key components and technical conditions, comparative examples 1-18 were designed. Their disadvantages were reflected by missing key components (such as cellulose and corrosion inhibitors) or exceeding the parameter range of the claims. The specific formulas and process parameters are shown in Tables 3 and 4.
[0049] Comparative Example 1
[0050] Different from Example 1, no lignocellulose was added, and the remaining steps were the same as Example 1.
[0051] Comparative Example 2
[0052] Different from Example 1, no corrosion inhibitor was added, and an equal amount of water (100 g) was used instead. The remaining steps were the same as Example 1.
[0053] Comparative Example 3
[0054] Different from Example 1, no pre-dispersion treatment of the nanomaterial is performed, and 3 g of nano-silicon dioxide is directly mixed with the dry mixed base material. The remaining steps are the same as Example 1.
[0055] Comparative Example 4
[0056] Different from Example 5, the particle size of the nano-silica is 50 nm (outside the claimed range of 10-30 nm), and the remaining steps are the same as Example 5.
[0057] Comparative Example 5
[0058] Different from Example 5, the mass ratio of nanomaterial to dispersant is 10:10 (beyond the claim range 3-6:10-20), and the remaining steps are the same as Example 5.
[0059] Comparative Example 6
[0060] Different from Example 5, the ultrasonic dispersion power is 1000W (beyond the claimed range of 500-800W), and the remaining steps are the same as Example 5.
[0061] Comparative Example 7
[0062] Different from Example 8, the nano-aluminum hydroxide solution was not vacuum impregnated into the lignocellulose, and 4-cyano-1H-1,2,3-triazole was directly added for reaction. The remaining steps were the same as those in Example 8.
[0063] Comparative Example 8
[0064] Different from Example 8, the amount of 4-cyano-1H-1,2,3-triazole used in the wood cellulose is 10 times the mass of the nanocellulose (3-6 times beyond the claimed range), and the remaining steps are the same as Example 8.
[0065] Comparative Example 9
[0066] Different from Example 8, the ultrasonic treatment power in the lignocellulose is 1000 W (exceeding the claimed range of 600-800 W), and the remaining steps are the same as Example 8.
[0067] Comparative Example 10
[0068] Different from Example 10, dopamine was not added in the preparation of the corrosion inhibitor, but was replaced by an equal amount of water. The remaining steps were the same as Example 10.
[0069] Comparative Example 11
[0070] Different from Example 10, the amount of ammonia solution used in the preparation of the corrosion inhibitor is 10 times the mass of ferrous sulfate (exceeding the scope of the claim by 3-7 times), and the remaining steps are the same as Example 10.
[0071] Comparative Example 12
[0072] Different from Example 10, the high temperature and high pressure reaction temperature in the preparation of the corrosion inhibitor is 200° C. (beyond the claimed range of 140-180° C.), and the remaining steps are the same as Example 10.
[0073] Comparative Example 13
[0074] Different from Example 12, bentonite is not added to the dry-mix base material, but is replaced by an equal amount of fly ash. The remaining steps are the same as Example 12.
[0075] Comparative Example 14
[0076] Different from Example 12, sodium nitrate was not added to the early strength agent, but an equal amount of sodium sulfate was used instead. The remaining steps were the same as Example 12.
[0077] Comparative Example 15
[0078] Different from Example 12, the stirring speed of the wet mixed slurry is 500 rpm (beyond the claimed range of 200-400 rpm), and the remaining steps are the same as Example 12.
[0079] Comparative Example 16
[0080] Different from Example 15, the amount of sulphoaluminate cement clinker in the dry mix base is 50 g (exceeding the claimed range of 20-40 g), and the remaining steps are the same as Example 15.
[0081] Comparative Example 17
[0082] Different from Example 15, the amount of wood cellulose used in the wet mixture is 5g (exceeding the claimed range of 1.5-3g), and the remaining steps are the same as Example 15.
[0083] Comparative Example 18
[0084] Different from Example 15, the amount of corrosion inhibitor in the wet mixed slurry is 15 g (exceeding the claimed range of 5-10 g), and the remaining steps are the same as Example 15.
[0085] The following are the formulas and process parameters of Examples 1-15 and Comparative Examples 1-18, in grams (g).
[0086] Table 1: Formulations and process parameters of Examples 1-8
[0087]
[0088]
[0089]
[0090]
[0091] Table 2: Formulations and process parameters of Examples 9-15
[0092]
[0093]
[0094]
[0095]
[0096] Table 3 Comparative Examples 1-9 formulations and process parameters
[0097]
[0098]
[0099]
[0100]
[0101]
[0102] Table 4 Comparative Examples 10-18 formulations and process parameters
[0103]
[0104]
[0105]
[0106]
[0107] Comparative Examples 1-18 demonstrate the necessity of key components and technical requirements in the following ways: Missing key components, such as in Comparative Example 1 (no lignocellulose), Comparative Example 2 (no corrosion inhibitor), and Comparative Example 3 (no pre-dispersion of nanomaterials), may result in reduced dispersion resistance, strength, or durability. Parameters out of range, such as in Comparative Example 4 (nanomaterial particle size out of range), Comparative Example 5 (nanomaterial to dispersant ratio out of range), and Comparative Example 6 (ultrasonic power out of range), may lead to nanomaterial agglomeration or uneven dispersion. Missing or altered processes, such as in Comparative Example 7 (no alumina impregnation of lignocellulose) and Comparative Example 10 (no dopamine in the corrosion inhibitor), may reduce the fiber-matrix bond or corrosion inhibition effectiveness. Excessive components, such as in Comparative Example 8 (excess triazole), Comparative Example 11 (excess ammonia), Comparative Example 17 (excess lignocellulose), and Comparative Example 18 (excess corrosion inhibitor), may lead to unbalanced material properties or increased costs. Adjustment of other components: such as Comparative Example 13 (no bentonite), Comparative Example 14 (single component of early strength agent), and Comparative Example 16 (excessive cement) may affect the anti-dispersion property, early strength, or slurry fluidity.
[0108] To comprehensively evaluate the performance of underwater, high-strength, anti-dispersion grouting materials, the following test methods were designed to cover anti-dispersion, mechanical properties, durability, and workability. These test methods reference national standards (such as GB / T50448-2015, "Technical Specification for the Application of Cement-Based Grouting Materials") to ensure scientific and reasonable results.
[0109] Anti-dispersion loss rate (%)
[0110] Test Method: Conducted in accordance with the "Test Procedure for Underwater Non-Dispersible Concrete" (DL / T5117-2000). The prepared slurry was injected into a test apparatus simulating an underwater environment (flow velocity 1.5 m / s). The lost solid particles were collected, dried, and weighed. Anti-dispersibility loss rate = (mass of lost solids / mass of initial slurry solids) × 100%. Test Conditions: Water flow velocity 1.5 m / s, ambient temperature 25 ± 1°C, test duration 30 minutes. Significance: Evaluates the stability of the slurry in dynamic water flow, with a target value of <5%.
[0111] 1d compressive strength (MPa, 5℃)
[0112] Test Method: Refer to the "Test Method for Cement Mortar Strength" (GB / T17671-2021). Prepare 40×40×160mm specimens at 5°C. After curing for one day, test the compressive strength using a universal testing machine. Test Conditions: Curing temperature 5°C, relative humidity 95±5%. Significance: Reflects the early strength of the mortar at low temperatures, with a target value >15MPa.
[0113] 28d compressive strength (MPa)
[0114] Test Method: Same as the 1-day compressive strength test, except that the specimens are cured for 28 days under standard curing conditions (20±2°C, relative humidity ≥95%). Test Conditions: Standard curing for 28 days. Significance: Evaluates the long-term strength of the slurry, with a target value of >60 MPa.
[0115] Chloride ion diffusion coefficient (×10 -12 m 2 / s)
[0116] Test method: The rapid chloride ion migration coefficient method (RCM method, NTBUILD492) was used. 100×50 mm cylindrical specimens were prepared, cured for 28 days, and then placed in a chloride ion diffusion apparatus. The chloride ion penetration depth was measured and the diffusion coefficient was calculated.
[0117] Test conditions: Test temperature 20±2℃, sodium chloride solution concentration 3.5%. Significance: Reflects the durability of the slurry, target value <1.8×10 -12 m 2 / s.
[0118] Porosity (%)
[0119] Test Method: Mercury intrusion porosimetry (MIP) is used to measure the pore structure of 28-day-cured specimens using an automated mercury intrusion porosimeter. Samples are vacuum dried after collection, with a test pressure range of 0.01-400 MPa. Test Conditions: Samples are dried to constant weight, and the test temperature is 25°C. Significance: This test assesses the density of the slurry, with a target value of <9.5%.
[0120] Yield stress (Pa)
[0121] Test method: Use a rotational rheometer to measure the rheological properties of the fresh slurry, and use the Herschel-Bulkley model to fit and calculate the yield stress. Test conditions: Test temperature 25±1℃, shear rate 0.1-100s -1 . Significance: Reflects the fluidity of the slurry, with a target value of approximately 32Pa.
[0122] Thixotropic index
[0123] Test method: Use rheometer to test thixotropy, record the slurry under high shear (100s-1 ) and then resume low shear (0.1s -1 ) and calculate the thixotropic index (recovery viscosity / initial viscosity). Test conditions: 25±1°C, three shear cycles. Significance: Evaluates the slurry's construction stability, with a target value of approximately 4.7.
[0124] Initial setting time (h)
[0125] Test Method: Measure the initial setting time of cement slurry using a Vicat apparatus in accordance with the "Test Methods for Water Consumption, Setting Time, and Soundness of Cement at Standard Consistency" (GB / T1346-2011). Test Conditions: Test temperature 20±2°C, relative humidity ≥90%. Significance: Reflects the application window of the slurry, with a target value of <12 hours.
[0126] 28d shrinkage (%)
[0127] Test Method: 25 × 25 × 280 mm specimens were prepared in accordance with the "Concrete Shrinkage Test Method" (GB / T50082-2009). After 28 days of standard curing, the length change rate was measured using a non-contact displacement meter. Test Conditions: Curing Temperature 20 ± 2°C, Relative Humidity 60 ± 5%. Significance: Evaluates the volume stability of the slurry, with a target value of < 0.08%.
[0128] Corrosion current density (μA / cm 2 )
[0129] Test Method: Using an electrochemical workstation, the Tafel polarization curve method was used to determine the corrosion current density of steel bars in slurry. The specimen was a 100×50mm cylinder with a 10mm steel bar embedded within. The test was conducted after 28 days of curing. Test Conditions: 3.5% sodium chloride solution, test temperature 25±1°C. Significance: Evaluates the corrosion protection effect of the corrosion inhibitor, with a target value of <0.8μA / cm 2 .
[0130] Table 5 Test results of anti-dispersion, strength and durability of Examples and Comparative Examples
[0131]
[0132]
[0133]
[0134] Table 6 Construction performance and durability test results of the embodiments and comparative examples
[0135]
[0136] Results Analysis: In Examples 1-15, the anti-dispersion loss rate was <5% (3.6-4.3%), significantly lower than the 25% of conventional materials. This is attributed to the pre-dispersion of the nanomaterials and the three-dimensional network structure of the cellulose fibers. Strength: The 1-day compressive strength (5°C) was 15.7-16.7 MPa, and the 28-day compressive strength was 61.9-66.0 MPa, meeting the requirements for rapid repair (>15 MPa) and long-term service (>60 MPa), attributed to the synergistic effect of the early strength agent and the expansion agent. Durability: The chloride ion diffusion coefficient was 1.4-1.8×10 - 12 m 2 / s, porosity 8.6-9.4%, indicating excellent density and resistance to chloride ion penetration, and significant multi-layer protection effect of the corrosion inhibitor. Construction performance: Yield stress of approximately 30.6-32.7Pa, thixotropic index 4.5-4.9, initial setting time 9.3-10.3h, indicating good fluidity and a suitable construction window period. Volume stability and corrosion resistance: 28d shrinkage rate 0.05-0.09%, corrosion current density 0.4-0.8μA / cm 2 , showing excellent volume stability and steel bar protection capabilities. In Comparative Examples 1-18, key components are missing: Comparative Example 1 (no lignocellulose), Comparative Example 2 (no corrosion inhibitor), and Comparative Example 3 (no nano-dispersion) have significantly reduced performance, with anti-dispersion loss rates as high as 17.8-25.4%, and strength and durability far below the target values, verifying the necessity of these components. Parameters out of range: Comparative Example 4 (nano-silica particle size 50nm), Comparative Example 5 (improper proportion of nanomaterials), Comparative Example 6 (excessive ultrasonic power), etc., have poor performance due to agglomeration or uneven dispersion, with anti-dispersion loss rates of 15.5-19.5% and porosity of 15.5-18.2%. Process missing: Comparative Example 7 (no alumina impregnation) and Comparative Example 8 (excessive triazole) have reduced compressive strength and durability due to insufficient interfacial bonding. Excess components: Although there is a slight improvement in Comparative Example 16 (excessive cement), Comparative Example 17 (excessive lignocellulose), and Comparative Example 18 (excessive corrosion inhibitor), they are still far inferior to the examples. The yield stress and initial setting time are abnormal, which affects the construction performance. Examples 1-15 are superior to the comparative examples in all aspects through processes such as nanomaterial pre-dispersion, lignocellulose modification, and corrosion inhibitor molecular design, meeting the high requirements of underwater engineering for anti-dispersion, strength, durability, and construction performance. The performance defects of the comparative examples further verify the necessity of key components and process parameters. The test results are consistent with the performance targets mentioned in the patent background (such as anti-dispersion loss rate <5%, 28-day compressive strength >60MPa, chloride ion diffusion coefficient ≤1.8×10 -12 m 2 / s) are highly consistent, demonstrating the technological advancement and practicality. Overall, excellent anti-dispersion properties are achieved through pre-dispersion of nanomaterials: Nano-silica (particle size 10-30nm), nano-iron oxide (particle size 20-50nm), or nano-alumina (particle size 15-40nm) is mixed with a dispersant (polyether or zwitterionic water reducer) and water in a mass ratio of (3-6): (10-20): (60-100) using ultrasonic dispersion technology. The mixture is then dispersed at a power of 500-800W and a frequency of 40-60kHz for 10-30 minutes to produce a stable nano-dispersion. The uniform dispersion of the nanomaterials significantly enhances the grout's anti-dispersion properties underwater, preventing the material from being washed away by the water flow. Introduction of lignocellulose: Lignocellulose is prepared from agricultural waste (such as rice husks or wheat straw). Nanocellulose with a diameter of 10-50 nm and an aspect ratio greater than 30 is produced through enzymatic hydrolysis (cellulase, 45-50°C, pH 4.5-5.0, 2-3 hours), ultrasonic treatment (600-800W, 20kHz, 10-15 minutes), vacuum impregnation (nanoaluminum hydroxide solution, 0.1-0.3MPa, 30-60 minutes), and microwave curing (800W, 3-5 minutes). This process is followed by modification with 4-cyano-1H-1,2,3-triazole (at a dosage of 3-6 times the mass of the nanocellulose) to further enhance its binding strength to the matrix. The addition of lignocellulose effectively improves the cohesion and crack resistance of the grouting material, thereby significantly enhancing its underwater anti-dispersion properties. High Strength: Matrix material formulation: 20-40 parts by weight of sulfoaluminate cement clinker (providing rapid hydration and early strength) or Portland cement (20-40 parts by weight, providing long-term strength) is combined with ultrafine mineral powder (6-12 parts by weight), activated steel slag or silica fume (4-10 parts by weight), fly ash or ultrafine fly ash (10-25 parts by weight), and bentonite (1-3 parts by weight). Mix in a spiral mixer at 50-100 rpm for 5-10 minutes to form a uniform dry mix. The optimal proportion of these materials provides a high-strength foundation for the grout. Application of an accelerator: This accelerator consists of 5-10 parts by weight of sodium sulfate, sodium formate, and sodium nitrate in a mass ratio of (0.4-1): (0.5-1.5): (0.5-1). This accelerates cement hydration and significantly improves the early strength of the grout, meeting the requirements for rapid repair of underwater projects. The role of the expansion agent: quicklime (3-7 parts by weight) acts as an expansion agent, which produces moderate expansion during the hydration process, compensates for the shrinkage of the grouting material, and improves the volume stability and later strength.Excellent durability: Preparation and application of the corrosion inhibitor: The corrosion inhibitor is prepared by mixing ferrous sulfate, ferrous chloride, and water in a mass ratio of 1:(1-1.5):(80-100), heating in a 60-80°C water bath, adding an aqueous ammonia solution (3-7 times the mass of the ferrous sulfate) and diethyl carbonate (2-4 times the mass of the ferrous sulfate), stirring, and reacting at 140-180°C under high pressure for 6-12 hours. Ethyl orthosilicate, dopamine, and sodium iodate are then added for subsequent treatment. The corrosion inhibitor (5-10 parts by weight) effectively inhibits steel corrosion in underwater environments, significantly improving the durability and long-term stability of the grouting material. Excellent workability: Optimized wet-mix slurry preparation: By controlling the mass ratio of water, mixture, and corrosion inhibitor to 1:(0.25-0.35):(0.05-0.1), stirring at 200-400 rpm for 3-5 minutes, and maintaining the temperature at 30-40°C, the grout's fluidity and workability are optimized, ensuring ease of pouring and forming in underwater environments. Compared to existing technologies, as shown by comparing Examples 1-15 with Comparative Examples 1-18 (e.g., Comparative Example 1 lacks lignocellulose, Comparative Example 2 lacks corrosion inhibitor, and Comparative Example 3 lacks pre-dispersed nanomaterials), the present invention significantly improves anti-dispersion (preventing material loss in water), early and late strength (meeting requirements for rapid repair and long-term service), and durability (superior corrosion resistance). Furthermore, precise control of process parameters avoids imbalances in material properties and ensures ease of construction.
[0137] The underwater, anti-dispersion, high-strength grouting material of this invention achieves excellent overall performance in underwater environments through the synergistic effects of nanomaterials, lignocellulose, an accelerator, an expansion agent, and a corrosion inhibitor, combined with an optimized preparation process. Its significantly improved anti-dispersion properties, high strength, durability, and workability make it an ideal material for underwater engineering repair and reinforcement.
[0138] The above content is a further detailed description of the present invention in conjunction with specific implementation methods. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, they can make several simple deductions or substitutions without departing from the concept of the present invention, which should be regarded as falling within the scope of protection determined by the claims submitted for the present invention.
Claims
1. A method for preparing an underwater anti-dispersion high-strength grouting material, characterized by: The method comprises the following steps: (1) pre-dispersion treatment of nanomaterials: selecting nanomaterials, wherein the nanomaterials are nano-silicon dioxide, nano-iron oxide or nano-aluminum oxide, adding dispersant and water, and dispersing by ultrasonication to prepare nano-dispersion liquid; (2) dry mixing preparation of matrix materials: weighing 20-40 parts by weight of sulphoaluminate cement clinker or silicate cement, 6-12 parts by weight of ultrafine mineral powder, 4-10 parts by weight of active steel slag or silica fume, 10-25 parts by weight of fly ash or ultrafine fly ash, and 1-3 parts by weight of bentonite in proportion, mixing them in a spiral mixer, and forming a nano-dispersion liquid. to form a uniform dry mixed base material; (3) wet mixing of the mixture: adding the nano-dispersion prepared in step (1) to the dry mixed base material formed in step (2), and simultaneously introducing an early strength agent, an expansion agent, lignocellulose, and a retarder, followed by stirring to obtain a mixture; (4) optimized preparation of a wet mixed slurry: adding water, the mixture obtained in step (3), and a corrosion inhibitor to a pulping device, controlling the mass ratio of water, the mixture, and the corrosion inhibitor to be 1: (0.25-0.35): (0.05-0.1), and then performing stirring and temperature control simultaneously to obtain a slurry.
2. The method for preparing the underwater anti-dispersion high-strength grouting material according to claim 1, characterized in that: The particle size of the nano-silicon dioxide in step (1) is 10-30 nm; the particle size of the nano-iron oxide in step (1) is 20-50 nm; the particle size of the nano-aluminum oxide in step (1) is 15-40 nm; and the dispersant in step (1) is a polyether water reducer or a zwitterionic water reducer.
3. The method for preparing the underwater anti-dispersion high-strength grouting material according to claim 1, characterized in that: The parameters of ultrasonic dispersion in step (1) are as follows: power 500-800 W, frequency 40-60 kHz, time 10-30 min; the mass ratio of the nanomaterial, dispersant and water in step (1) is (3-6): (10-20): (60-100).
4. The method for preparing the underwater anti-dispersion high-strength grouting material according to claim 1, characterized in that: In step (2), the rotation speed of the spiral stirrer is 50-100 rpm, and the mixing time is 5-10 min.
5. The method for preparing the underwater anti-dispersion high-strength grouting material according to claim 1, characterized in that: The mass ratio of the dry mixed base material, nano-dispersion, early strength agent, expansion agent, lignocellulose and retarder in step (3) is 100: (1.5-4): (5-10): (3-7): (1.5-3): (0.05-0.2); wherein the expansion agent is quicklime, wherein the aspect ratio of the lignocellulose is greater than 30, and wherein the retarder is sodium citrate; the preparation method of the lignocellulose in step (3) is as follows: agricultural waste rice husk or wheat straw is selected, water is added to obtain a slurry with a solid content of 3-5wt%, cellulase with a final mass percentage of 2% is added, and the mixture is reacted at 45-50°C and pH 4.5-5.0 for 2-3h, and a power of 600-800 is used. W, frequency 20kHz ultrasonic treatment for 10-15min, obtain nanocellulose with a diameter of 10-50nm and an aspect ratio greater than 30, prepare 10mM nano aluminum hydroxide solution and embed it into the microporous structure of nanocellulose by vacuum impregnation, the vacuum impregnation pressure is 0.1-0.3MPa, the time is 30-60min, followed by microwave assisted curing, the curing power is 800W, the time is 3-5min, then add 4-cyano-1H-1,2,3-triazole 3-6 times the mass of nanocellulose and water 30-40 times the mass of nanocellulose, control the reaction conditions to 60-80℃, the time is 1-2h, and vacuum drying is performed to obtain.
6. The method for preparing the underwater anti-dispersion high-strength grouting material according to claim 1, characterized in that: The early strength agent in step (3) is a mixture of sulfate, formate and nitrate in a mass ratio of (0.4-1): (0.5-1.5): (0.5-1); the stirring speed in step (3) is 100-200 rpm, and the stirring time is 5-8 minutes.
7. The method for preparing the underwater anti-dispersion high-strength grouting material according to claim 1, characterized in that: The stirring speed in step (4) is 200-400 rpm, and the stirring time is 3-5 min; the temperature controlled in step (4) is 30-40°C.
8. The method for preparing the underwater anti-dispersion high-strength grouting material according to claim 1, characterized in that: The preparation method of the corrosion inhibitor in step (4) is as follows: ferrous sulfate, ferrous chloride and water are mixed in a mass ratio of 1: (1-1.5): (80-100), heated in a water bath to 60-80°C, then added with a 20% ammonia solution with a mass percentage of 3-7 times the mass of ferrous sulfate and diethyl carbonate with a mass percentage of 2-4 times the mass of ferrous sulfate, stirred at 200-300 rpm for 10-20 minutes, then transferred to a high-temperature and high-pressure reactor, reacted at 140-180°C for 6-12 hours, After cooling, the supernatant is recovered, ethyl orthosilicate in an amount of 0.1-0.2 times the mass of the supernatant is added, and the mixture is shaken at 60 rpm overnight to obtain a primary product after drying. Then, water in an amount of 80-150 times the mass of the primary product is added, and the pH is adjusted to 5. Dopamine in an amount of 0.2-0.6 times the mass of the primary product and sodium iodate in an amount of 0.1-0.2 times the mass of the primary product are added, and the mixture is stirred and mixed. The mixture is reacted in a microwave oven at 200-300 W for 5-15 minutes, and the mixture is naturally cooled and dried to obtain a final product.
9. An underwater anti-dispersion high-strength grouting material, characterized in that: The underwater anti-dispersion high-strength grouting material is obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
High-performance grouting material for prefabricated buildings and preparation method thereof
CN111170693A
Composite cement-based high-temperature flowing water grouting material and preparation method thereof
CN115321927A
Dispersion-resistant and high-impermeability grouting material under flowing water condition as well as preparation method and application thereof
CN115504747A
High-strength anti-fatigue load steel-concrete connection grouting material and preparation method thereof
CN115925350A
Underwater anti-dispersion additive and anti-dispersion cement-based grouting material thereof
CN119874250A